Self-management and HeAlth Promotion in Early-stage dementia with e-learning for carers (SHAPE): study protocol for a multi-centre randomised controlled trial - Ingelin Testad; Linda Clare; Kaarin Anstey; Geir Selbæk; Guro Hanevold Bjørkløf; Catherine Henderson; Ingvild Dalen; Martha Therese Gjestsen; Shelley Rhodes; Janne Røsvik; Jessica Bollen; Jessica Amos; et al. (BMC, 2020)
Abstract Background With an increasing number of people with dementia worldwide and limited advancement in medical treatments, the call for new and cost-effective approaches is crucial. The utility of self-management has been proven in certain chronic conditions. However, very little work has been undertaken regarding self-management in people with dementia. Methods The SHAPE trial will include 372 people with mild to moderate dementia to evaluate the effectiveness and cost-effectiveness of an educational programme combining approaches of self-management, health promotion, and e-learning for care partners. The study is a multi-site, single-randomised, controlled, single-blinded trial with parallel arms. The intervention arm is compared with treatment as usual. The intervention comprises a 10-week course delivered as group sessions for the participants with dementia. The sessions are designed to develop self-management skills and to provide information on the nature of the condition and the development of healthy behaviours in a supportive learning environment. An e-learning course will be provided for care partners which covers similar and complementary material to that discussed in the group sessions for the participant with dementia. Discussion This trial will explore the effect of the SHAPE group intervention on people with mild to moderate dementia in terms of self-efficacy and improvement in key health and mental health outcomes and cost-effectiveness, along with carer stress and knowledge of dementia. Trial registration ClinicalTrials.gov Identifier: NCT04286139, registered prospectively February 26, 2020, https://clinicaltrials.gov/ct2/show/NCT04286139